State Space Modeling and Small Signal Stability Analysis of Synchronous Generator with Fuzzy based AVR - Ramya R; Selvi K (International Journal of Electrical and Computer Engineering (IJECE), 2012)
This paper presents a linear mathematical model of a Synchronous Generator with excitation system for small signal stability analysis. This work aims to develop a controller based on fuzzy logic to simulate an Automatic Voltage Regulator (AVR) for a synchronous generator. The performance of fuzzy based AVR is tested on Single Machine connected to an Infinite Bus bar system (SMIB) in the MATLAB/SIMULINK platform and the results are compared with the IEEE Exciter model.DOI:http://dx.doi.org/10.11591/ijece.v2i6.1524